2014
DOI: 10.1098/rstb.2013.0096
|View full text |Cite
|
Sign up to set email alerts
|

Role of anoctamins in cancer and apoptosis

Abstract: Anoctamin 1 (TMEM16A, Ano1) is a recently identified Ca 2+ -activated chloride channel and a member of a large protein family comprising 10 paralogues. Before Ano1 was identified as a chloride channel protein, it was known as the cancer marker DOG1. DOG1/Ano1 is expressed in gastrointestinal stromal tumours (GIST) and particularly in head and neck squamous cell carcinoma, at very high levels never detected in other tissues. It is now emerging that Ano1 is part of the 11q13 locus, amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 64 publications
5
83
0
Order By: Relevance
“…A pro-proliferative role of ANO1 is found in most cancer cells investigated 118,[141][142][143][144][145][146] and Stanich and coworkers demonstrated that ANO1 regulates cell proliferation at the G1/S transition in the cell cycle. 147 Other studies, however, show that cell proliferation in certain cell types is unaffected by ANO1, e.g.…”
Section: Proliferationmentioning
confidence: 99%
See 3 more Smart Citations
“…A pro-proliferative role of ANO1 is found in most cancer cells investigated 118,[141][142][143][144][145][146] and Stanich and coworkers demonstrated that ANO1 regulates cell proliferation at the G1/S transition in the cell cycle. 147 Other studies, however, show that cell proliferation in certain cell types is unaffected by ANO1, e.g.…”
Section: Proliferationmentioning
confidence: 99%
“…140 ANO6 has received more attention in relation to apoptosis compared to ANO1 and in particular its role as a putative scramblase involved in the redistribution of phospholipids between the outer/inner membrane during apoptosis. 118,152,153 siRNA K D of ANO6 reduces cisplatin induced Caspase 3 activation (apoptosis) in ELA cells (Fig. 15) and staurosporine induced cell death in lung epithelial cells (A549 151 ).…”
Section: Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Cl 2 channels important for cell proliferation, cell migration and metastasis further include anoctamin 1 (TMEM16A, Ano1), which is activated by the increase in cytosolic Ca 2þ activity [127]. Ano1 expression is excessive in several gastrointestinal stromal tumours [127].…”
Section: Anion Channelsmentioning
confidence: 99%